Harmonious Complementarity in Leadership: A Necessary Tool for Environment and Sustainability - Ikegbu, Ephraim Ahamefula (European Journal of Sustainable Development, 2017)
This paper seeks to argue that harmonious complementarity in leadership remains a necessary tool that will navigate environmental consciousness and sustainable development in Nigeria. The choice of harmonious complementarity in leadership is pragmatically intended to utilize the facilities of local circumstance to address the confronting challenges of our existence. Harmonious complementarity in this context, implies the socio-cultural integration, co-operation and cross fertilization of natural and gifted ideas by the people within a defined political entity for the purpose of confronting a task that is before them. Under this ideal and leadership construction, the collective opinions of the people are sought and the consciousness of sustaining, protecting, preserving and/or promoting the environment becomes the collective task of the people; both the leader and the led. This is because environmental consciousness and positive awareness by the leadership would have risen to the climax that inappropriate laws and policies that were impairing sustainable development and negative activities of the human elements on the environment will be a relic of the past. This paper shall employ analytic and rational methods to drive home its argument. Keywords: Harmonious Complementarity, Leadership, Sustainability, Environment